Encounters with borders: A migrant academic’s experiences of the visa regime in the Global North - Dixit, Priya (Learning and teaching, 2021)
This article examines (im)obility in the global visa regime through the experiences of a Global South academic working in the Global North. Drawing on an autoethnographic account of a visa application, this article outlines the ways in which the global visa regime negatively affects a Global South academic’s life. Visa regulations constitute a particular Global South academic subject in the Global North, one whose academic career is characterised by uncertainty and anxiety, as visas can limit access to promotions and to fieldwork and research opportunities. Visa experiences can thus contribute to alienation and non-belonging of Global South scholars in academia, while impacting knowledge production and teaching.